REBUS93 - Rehabilitation survey in Stockholm county 1993 - REBUS93 - Urval av fp till REBUS1993 - Lundin, Andreas; Theobald, Holger; Torgén, Margareta (Karolinska Institutet, 2007)
REBUS-93 meant that data collected on the work, leisure and family situation of the REBUS survey 1969/70, together with retroactively collected information on physical and psychosocial working conditions for the years 1970 to 1993 could be tested as independent factors for musculoskeletal morbidity, mental symptoms and low functionality 24 years later, i.e. a lifetime perspective could be put on found relationships.

Purpose:

The purpose of REBUS-93 was to identify risk factors for musculoskeletal disorders, mental symptoms and low physical function.

REBUS-93 innebar att data insamlade om arbets- fritids- och familjesituation vid REBUS-undersökningen 1969/70, tillsammans med retroaktivt insamlad information om fysiska och psykosociala arbetsförhållanden för åren 1970 till 1993, kunde prövas som oberoende faktorer för muskuloskeletal sjuklighet, psykiska symtom och låg funktionsförmåga 24 år senare, d v s ett livstidsperspektiv kunde läggas på funna samband.

Syfte:

Syftet med REBUS-93 var att identifiera riskfaktorer för muskuloskeletala besvär, psykiska symptom och låg fysisk funktionsförmåga
REBUS93 - Rehabiliteringsundersökningen i Stockholms län 1993 - REBUS93 - Urval av fp till REBUS1993
Keywords: gender; genus; life events; livshändelser; Leisure Activities; Fritidsaktiviteter; Physical Fitness; Fysisk kondition; Neck; Hals; Back; Rygg; Pain; Smärta; Muscle Strength; Muskelstyrka; Pain Threshold; Smärttröskel; age; ålder; employment and environment; sysselsättning och miljö; family; familj; balance (economic); balans; work environment; arbetsmiljö; profession; yrkestillhörighet; physical working conditions; fysiska arbetsförhållanden; computing; datorarbete; psychosocial working conditions; psykosociala arbetsförhållanden; exercise habits; motionsvanor; mental disorders; psykiska besvär; musculoskeletal disorders; muskuloskeletala besvär; shoulders; axlar; muscular endurance; muskulär uthållighet; oxygen uptake; syreupptagningsförmåga; neurosensory; neurosensorik; perception thresholds; perceptionströsklar; fine motor skill; finmotorik; mental function; psykisk funktionsförmåga; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap